2009
DOI: 10.1097/pgp.0b013e31819b2864
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Value of Morphometric and DNA Flow Cytometric Variables as Independent Predictors of Survival in Epithelial Ovarian Carcinoma: A 5-year Follow-up Study

Abstract: The aim of this follow-up study is to validate the clinical significance of quantitative morphometric and DNA flow cytometric variables as independent prognostic factors of overall survival and progression-free survival in epithelial ovarian carcinoma. Tumor samples were collected from 135 patients with epithelial ovarian carcinoma at 3 hospitals in the Netherlands. Evaluated clinico-pathologic variables were age, histologic subtype, differentiation grade, clinical stage [International Federation of Gynecology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…Our study showed significant positive correlation between DNA content and nuclear area in all serous and mucinous groups. These results came similar to those of Veerman et al, 2009 [ 19 ] who also showed that DNA ploidy and MNA (Mean Nuclear Area) were of significant prognostic value. Also, Lassus et al, 2011 [ 40 ] stated that DNA aneuploidy is a strong predictor of poor prognosis in serous ovarian carcinoma.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study showed significant positive correlation between DNA content and nuclear area in all serous and mucinous groups. These results came similar to those of Veerman et al, 2009 [ 19 ] who also showed that DNA ploidy and MNA (Mean Nuclear Area) were of significant prognostic value. Also, Lassus et al, 2011 [ 40 ] stated that DNA aneuploidy is a strong predictor of poor prognosis in serous ovarian carcinoma.…”
Section: Discussionsupporting
confidence: 91%
“…DNA ploidy and/or S-phase fraction have been used as biologic predictors of aggressive behaviour in a variety of solid tumours [ 17 ]. Recently, attention has focused on borderline lesions to determine if flow cytometry plays a role in separating potentially aggressive tumours from those which will pursue a more innocuous course [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In malignant tumors, the nuclear size is usually larger and more irregular in high-grade (HG) tumors as compared to benign lesions and is a reflection of DNA content, ploidy, and active proliferation. Nuclear morphometric study is one of the techniques to evaluate the tumors and their grades [4,5]. Computer-assisted image morphometry provides high-precision measurement of several variables, characterizing the size and shape of nuclei.…”
Section: Introductionmentioning
confidence: 99%